(untitled) (Revista Tempo e Argumento, 2016)
This article addresses the visual and verbal discourses of mainstream press in the context of the 1964 Brazilian Coup, with an emphasis on the ‘secondary target’ of the purges undertaken by the new regime, namely, corruption. The study analyzes the role played by periodicals – especially caricatures – in building representations that provided the dictatorship with support, mainly regarding the fight against corruption. In order to adequately approach the object, we try to grasp the political aims and discursive manipulations of the players involved, who were often driven by reasons very far from fighting against corruption. Keywords: Caricature; Politics; Dictatorship; Brazil – History – 1964 - 1985.